A Pathogenesis-Related Protein-Like Gene Is Involved in the Panax notoginseng Defense Response to the Root Rot Pathogen - Li, Shan; Wang, Zie; Tang, Bifeng; Zheng, Lilei; Chen, Hongjun; Cui, Xiuming; Ge, Feng; Liu, Diqiu (Frontiers in Plant Science, 2021)
Pathogenesis-related proteins (PRs) are a class of proteins that accumulate in response to biotic and abiotic stresses to protect plants from damage. In this study, a gene encoding a PR-like protein (PnPR-like) was isolated from Panax notoginseng, which is used in traditional Chinese herbal medicines. An analysis of gene expression in P. notoginseng indicated that PnPR-like was responsive to an infection by the root rot pathogen Fusarium solani. The expression of this gene was induced by several signaling molecules, including methyl jasmonate, ethephon, hydrogen peroxide, and salicylic acid. The PnPR-like-GFP fusion gene was transiently expressed in onion (Allium cepa) epidermal cells, which revealed that PnPR-like is a cytoplasmic protein. The purified recombinant PnPR-like protein expressed in Escherichia coli had antifungal effects on F. solani and Colletotrichum gloeosporioides as well as inhibited the spore germination of F. solani. Additionally, the in vitro ribonuclease (RNase) activity of the recombinant PnPR-like protein was revealed. The PnPR-like gene was inserted into tobacco (Nicotiana tabacum) to verify its function. The gene was stably expressed in T2 transgenic tobacco plants, which exhibited more RNase activity and greater disease resistance than the wild-type tobacco. Moreover, the transient expression of hairpin RNA targeting PnPR-like in P. notoginseng leaves increased the susceptibility to F. solani and decreased the PnPR-like expression level. In conclusion, the cytoplasmic protein PnPR-like, which has RNase activity, is involved in the P. notoginseng defense response to F. solani.